Children's concept of death and death anxiety in relation to cognitive development. - Dugang, Dianen Rio D.
This study examined children's understanding of death and level of death anxiety in relation to their cognitive development. Thirty (30) children aging four (4) to twelve (12) years old in Molo I Elementary School were selected through random sampling for this study. Three (3) instruments were utilized namely: Concepts of Death Interview (Jay et al., 1948), Death Interview for Children (Slaughter & Griffiths, 2007), and Death Anxiety Scale (Abdel-Khalek, 2012). Results showed that children concepts of death varied as they grow older and as cognitive development stage change. On the other hand, death anxiety was positively correlated with age which means as children cognitively developed their fear of death increased.